Peningkatan Kemandirian Belajar Matematika Materi Konsep Segi Empat Dan Segitiga Dengan Metode RBL Pada Siswa SMPN 91 - Yulis, Ratna (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
This research examines the learning model of Resource Based Learning is not something new for teachers at all. The Resource Based Learning learning model prioritizes cooperation in solving problems to apply knowledge and skills in order to achieve learning objectives. The research setting was at SMP Negeri 91 East Jakarta with 36 class VII-C students as subjects. The research was conducted for 2 cycles. With 3 meetings each cycle. The conclusions obtained from this study are that when referring to the results of initial observations before using the Resource Based Learning method, it was found that only 27.72% of students could have the ability to work on row and row material well. After the research was carried out by giving the Resource Based Learning method, in cycle 1 there was an increase of 72.22% at the end of the cycle students were able to work on series and line material, then in cycle 2 as many as 94.66% of students were able to work on series and line material and found increased learning outcomes in mathematics due to the Resource Based Learning method.